2020
DOI: 10.1088/1742-6596/1567/4/042096
|View full text |Cite
|
Sign up to set email alerts
|

Effective gamma irradiation dose on viscosity and molecular weight reduction of chitosan

Abstract: Chitosan is a potential natural blood lead chelating agent. In order to improve its chelating capability, the solubility of chitosan must be enhanced. It is an essential property which is also closely related to molecular weight and viscosity. One of the most renowned and effective methods to reduce the molecular weight and viscosity of a certain particle is irradiation. This research aims to examine the effect of Gamma 60Co irradiation upon molecular weight and viscosity of chitosan. 80 mesh chitosan was irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…γ-irradiated microparticles exhibited a slightly higher drug release rate and low swelling capacity than the non-irradiated microparticles. By spectral characterization, it was shown that γ-irradiation of chitosan microparticles induced neither crosslinking nor formation of new groups in the chitosan matrix; the gamma rays induced only one kind of free radical in the chitosan matrix or reduction in average molecular weight [ 20 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…γ-irradiated microparticles exhibited a slightly higher drug release rate and low swelling capacity than the non-irradiated microparticles. By spectral characterization, it was shown that γ-irradiation of chitosan microparticles induced neither crosslinking nor formation of new groups in the chitosan matrix; the gamma rays induced only one kind of free radical in the chitosan matrix or reduction in average molecular weight [ 20 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…This research used pharmaceutical-grade Chitosan powder (CV Chimultiguna), made from the chitin of Crustacean shells, sized 80-100 Mesh, viscosity of 20-100 mPa s, with minimum degree of deacetylation at 94%. Chitosan was irradiated with Gamma Cobalt-60 ray from Gamma Chamber 400 A at the dosage of 150 kGy (Marianti et al, 2020). The irradiation process was performed in Center for Isotopes and Radiation Application (CIRA) BATAN Jakarta, Indonesia.…”
Section: Chitosan Irradiationmentioning
confidence: 99%
“…Irradiation is one of the effective methods to decrease chitosan size. A dosage of 150 kGy of cobalt-60 irradiation significantly reduces the molecular weight and viscosity of chitosan (Marianti, Anggraito, & Christijanti, 2020). This condition is mainly caused by the scission of glycosidic bond on deacetylation degree (72e75%) (Garcia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…With gamma irradiation, the viscosity and molecular weight of chitosan decrease in a dose-dependent manner [ 13 ]. This decrease is due to the depolymerization of chitosan chain through scission mechanism [ 14 ]. However, the characteristics of irradiated chitosan need to be evaluated to determine its effectiveness as a ruminant feed.…”
Section: Introductionmentioning
confidence: 99%